Work environment - Pollard, Jeannie (South Melbourne : Nelson, 1996)
This book is about: Structure of private and public organisations; Responsibilities and rights in the workplace; Equal opprtunity and anti-discrimination in the workplace; An outline of the Australian industral relations system; and Aspects of ongoing change in the workplace.
Keywords: Work environment; Business -- Problems, exercises, etc; Business; Work environment; Work environment -- Problems, exercises, etc